2016
DOI: 10.1002/chem.201602223
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Copper Guanidine Quinoline Complexes: Predicting the Activity of Catalysts in ATRP with DFT

Abstract: Copper complexes of the hybrid guanidine ligands 1,3-dimethyl-N-(quinolin-8-yl)-imidazolidin-2-imine (DMEGqu) and 1,1,3,3-tetramethyl-2-(quinolin-8-yl)-guanidine (TMGqu) have been studied comprehensively with regard to their structural and electrochemical properties and their activity in atom transfer radical polymerization (ATRP). A simple analysis of the molecular structures of the complexes gives no indication about their activity in ATRP; however, with the help of DFT and NBO analysis the influence of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 74 publications
10
52
0
Order By: Relevance
“…It is determined by the dihedral angles between the plane of three nitrogen atoms (N amine –N gua –N amine ) and the three carbon atoms (C amine –C gua –C amine ) of the guanidine unit. The twist angles of the guanidine moieties, which are closer to the aliphatic unit, are close to 34°, which has been found earlier for guanidines with TMG units , , , . In the guanidine moiety, which is closer to the aromatic unit, the guanidine twist is smaller.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It is determined by the dihedral angles between the plane of three nitrogen atoms (N amine –N gua –N amine ) and the three carbon atoms (C amine –C gua –C amine ) of the guanidine unit. The twist angles of the guanidine moieties, which are closer to the aliphatic unit, are close to 34°, which has been found earlier for guanidines with TMG units , , , . In the guanidine moiety, which is closer to the aromatic unit, the guanidine twist is smaller.…”
Section: Resultssupporting
confidence: 82%
“…Not only dinuclear copper complexes but also tri‐ and tetranuclear copper complexes were synthesised with aromatic guanidine ligands and were redox‐active as well , . Hybrid (guanidine)copper complexes displayed a good activity in atom transfer radical polymerisation (ATRP) underlined by DFT calculations . Moreover, it has been shown that aromatic bis(guanidine)copper complexes show a well‐controlled ATRP activity in the polymerisation of styrene .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the different coordination strength, the bond lengths for Zn-N gua (1.986(3), 2.013(4), 2.065(5) Å) are shorter than for Zn-N amine (2.053(3), 2.065(4), 2.041(5) Å). This trend can be seen in recent studies [69,78] • , in good agreement with the value expected for an ideal tetrahedral geometry of 90 • . All complexes are tetrahedrally distorted coordinated, which can be shown by the structural parameter τ 4 .…”
Section: Zinc Halide Complexessupporting
confidence: 88%
“…Due to the different coordination strength, the bond lengths for Zn-Ngua (1.986(3), 2.013(4), 2.065(5) Å) are shorter than for Zn-Namine (2.053(3), 2.065(4), 2.041(5) Å). This trend can be seen in recent studies [69,78]. The angle of ZnN2 is around 100° and the angle between the coordination planes {∡ (ZnX2, ZnN2)} is 80.3°-83.4°, in good agreement with the value expected for an ideal tetrahedral geometry of 90°.…”
Section: Zinc Halide Complexessupporting
confidence: 85%
See 1 more Smart Citation